A 15-Year Report on the Uneven Distribution of Women in Orthopaedic Surgery Residency Training Programs in the United States. Issue 2 (April 2021) - Van Heest, Ann E.; Agel, Julie; Samora, Julie Balch
Abstract : Background: This study was undertaken to update reports from 2004 to 2005 through 2008 to 2009, and 2009 to 2010 through 2013 to 2014, including 5 additional years of GME Track data. Our hypothesis is there have been no significant changes during the past 5 years in the distribution of Accreditation Council for Graduate Medical Education (ACGME)-accredited orthopaedics residency programs that train female residents, compared with the previous 10 years. Methods: Data for ACGME-accredited orthopaedics residency training programs in the United States were analyzed for 5 consecutive academic years (2014-2015 through 2018-2019). Programs were classified as having no women, 1 woman, 2 women, or greater than 2 women in training. Programs were analyzed for percentage of female residents and classified as having above the national average (>20%), similar to the national average (between 10 and 20%), or below the national average (<10%). Results: Analysis of the original 5 years (2004-2009) compared with the most recent data (2014-2019) demonstrated a statistically significant improvement in the number of programs training women (p < 0.001). From 2004 to 2009 to 2014 to 2019, the absolute number and percent of female trainees have increased (p < 0.001). Similar analysis of the middle 5 years (2009-2014) compared with the most recent 5 years (2014-2019) did not demonstrate a statistically significant change (p = 0.12). From 2014 to 2019, residency programs in the United States continue to train women at unequal rates: 37 programs had no female trainees, while 53 programs had >20% female trainees during at least one of these 5 years. Conclusions: Female medical students continue to pursue orthopaedics at rates lagging behind all other surgical specialties. Not all residency programs train women at equal rates. If the rate of training of female residents over the past 15 years were projected over time, we would not achieve 30% women within orthopaedics residency training programs until approximately 2060. Level of Evidence: III.